Pengaruh Kepatuhan Pelaporan Keuangan dan Whistleblowing terhadap Pencegahan Kecurangan - Qobid, Abdul; Zanaria, Yulita; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the effect of Financial Reporting Compliance and Whistleblowing on fraud prevention at PT BPR Lipat Ganda East Lampung. The type of research used in this study is quantitative research. This study uses a sampling technique in the form of purposive sampling. This study uses primary data through questionnaires, and the population in this study are employees of PT BPR Lipat Ganda East Lampung, totaling 30 employees. The data in this study were analyzed using the IBM SPSS 25 program. The results of this study indicate that Financial Reporting Compliance has a positive effect on Fraud Prevention, Whistleblowing has a positive effect on Fraud Prevention, and Financial Reporting Compliance and Whistleblowing simultaneously have a positive effect on Fraud Prevention at PT BPR Lipat Ganda East Lampung